Psychological burnout and its relationship to family adjustment among mothers of children with autism in centers for people with special needs in Khartoum - Al-Kashef, Sarah Mohamed Ahmed (Journal of Educational and Psychological Sciences, 2023)
The research aims to find out the correlation between psychological combustion and bad compatibility in the mothers of autistic children and its relationship to family compatibility. In her research, the researcher followed the correlative descriptive approach. 108 mothers of autistic children in special needs centres in Khartoum State (I am Sudan- Jude- Eddy does not tire of good manners) The psychological combustion scale and the family compatibility scale were used after being exposed to a group of arbitrators to find out the truthfulness of the paragraphs with the overall degree of sub- dimensions of the scale in the current research community, and then calculate Pearson’s correlation coefficient between the grades of each paragraph with the overall score of the scale. To analyze the evidence, the researcher followed the Statistical Package Program (SPSS) where the Alpha Kronbach coefficient used the Pearson correlation coefficient and the Single Contrast Test. Among the recommendations of the research are to raise the level of self- efficacy of autism spectrum disorder mothers through mentoring programmes and to make mentoring programmes to reduce their mothers’ feeling of psychological combustion.